2022
DOI: 10.1002/dmrr.3567
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six surrogate insulin resistance indexes for predicting the risk of incident stroke: The Rural Chinese Cohort Study

Abstract: Background and Purpose: Some cheap and easily used operated indexes of insulin resistance (IR) were currently available. We aimed to evaluate the association of six surrogate indexes of IR with incident stroke and to compare their predictive capacity. Methods:We analysed data from 14,595 eligible study participants from the Rural Chinese Cohort Study. Modified Poisson regression models were used to estimate relative risks (RRs) and 95% confidence intervals (95% CIs) of incident stroke associated with the visce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
4
12
0
Order By: Relevance
“…Many previous studies have shown an association between a higher TyG index and an increased incidence of atherosclerosis, intima media thickness of common carotid artery, unstable carotid plaque, hypertension, arterial stiffness, and cardiovascular disease [10][11][12][13]. As expected, a plenty of evidences proved that TyG index was independently associated with the occurrence of stroke, and a higher TyG index was also a predictor of all-cause mortality and poor outcomes in patients with acute ischemic stroke [14][15][16][17].…”
Section: Introductionsupporting
confidence: 54%
“…Many previous studies have shown an association between a higher TyG index and an increased incidence of atherosclerosis, intima media thickness of common carotid artery, unstable carotid plaque, hypertension, arterial stiffness, and cardiovascular disease [10][11][12][13]. As expected, a plenty of evidences proved that TyG index was independently associated with the occurrence of stroke, and a higher TyG index was also a predictor of all-cause mortality and poor outcomes in patients with acute ischemic stroke [14][15][16][17].…”
Section: Introductionsupporting
confidence: 54%
“…Consistent with our findings, Zhao et al. found CVAI associated with stroke based on rural population of a Chinese county ( 17 ). We additionally found linear association between CVAI and stroke using national data, which was in line with Zhang et al.…”
Section: Discussionsupporting
confidence: 92%
“…However, whether CVAI also predict incident CVD well among general population remains unclear. Studies based on rural population from a Chinese county or health examination population in a Beijing hospital reported positive associations between CVAI and stroke or coronary heart disease ( 17 , 18 ), respectively. Another study from a Chinese province showed that CVAI was positively associated with CVD in women but not in men ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhao et al have revealed independent associations between multiple IR surrogates and stroke incidence data from a rural Chinese cohort study, with CVAI identified as the most suitable predictor of stroke. 30 Another study has reported a strong association between CVAI and the risk of coronary heart disease, surpassing VAI in predicting risk among Asian populations. 31 Consistent with previous research, our analysis revealed that CVAI was the most accurate predictor of CMM, followed by Obesity increases the risk of cardiovascular metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhao et al. have revealed independent associations between multiple IR surrogates and stroke incidence data from a rural Chinese cohort study, with CVAI identified as the most suitable predictor of stroke 30 . Another study has reported a strong association between CVAI and the risk of coronary heart disease, surpassing VAI in predicting risk among Asian populations 31 .…”
Section: Discussionmentioning
confidence: 99%